Malnutrition, Poverty, and Economic Growth - Heltberg, Rasmus (2012)
This paper argues that indicators of anthropometric shortfall--especially low height and low weight-for-age--are uniquely suited for assessing absolute deprivation in developing countries. Anthropometric indicators are relatively precise, readily available for most countries, reflect the preferences and concerns of many poor people, consistent with reckoning the phenomenon directly in the space of functionings, intuitive, easy to use for advocacy, and consistent over time and across subgroups. Anthropometric indicators can therefore complement (but not replace) standard indicators of income/consumption poverty, especially for comparisons across subgroups, within households, across countries, and in the long run. In addition, the paper analyses spells of change in malnutrition over time, finding that the association between economic growth and chronic child malnutrition is very small (but statistically significant) and much lower than the elasticity of growth on poverty. The policy implication of this finding is that direct interventions aimed at reducing infant malnutrition are required.